Grundtvigs erkendelsesteori. Om forholdet mellem tro og fornuft i tidsskriftet »Danne-Virke« (1816-19). - Jensen, Henrik Fibæk (Grundtvig-Studier, 1979)
Grundtvig’s Theory of Knowledge. On the relationship between faith and reason in the journal ‘Danne-Virke’ (1816- 19) by Henrik Fibcek Jensen. By comparing a quotation from Grundtvig’s Diary from 1804 with an expression from H.C. Andersen’s Diary in 1872, Fibæk Jensen first demonstrates that the background for both notes is existential, corresponding to Søren Kierkegaard’s in ‘Fear and Trembling’ (Frygt og Bæven). Both for Grundtvig and for Kierkegaard the concept of God is a relatively uncomplicated pre-condition. The aging Andersen has become ‘too clever and unhappy’ to appreciate this. But Grundtvig wanted to combat the atheism that was gaining ground in many guises during his time. The problem first became serious in Denmark in the second half of the century. Grundtvig is not a particularly cogent thinker; he deliberately avoids putting existence into some sort of system, and this makes his arguments somewhat inconsecutive now and then. But to discuss them as home-made philosophy (Poul Behrendt) or mere aphorisms (F. Rønning) only denotes a lack of ability to compound Grundtvig’s various treatises into one. Grundtvig regards man as an organism, in which the truth that the individual link maintains must harmonize with the experiences that the rest of the organism continues to have, in order to verify that truth. The conclusion one reaches through reason must not only be free of contradictions but must also harmonize with the perception of the universe one creates through one’s immediate senses. Kierkegaard may be said to set free those tendencies that are straining at the leash in Grundtvig. Both operate with the body, the soul and the spirit and both believe that the three parts that go to make up man must be in the right relationship to one another and to the power that God has ordained to them, if man is to be said to have fulfilled his task. But here we find a decisive terminological difference; Grundtvig calls the superior part of man the Soul (the Self), whereas Kierkegaard calls the superior part the Spirit (the Self). For Kierkegaard man is given directly by God’s hand, so that the soul and the body of the child are placed in the proper relationship to one another, whilst the spirit is for the time being ‘slumbering’. The raising of the spirit’s consciousness makes itself felt in fear, dizziness and feelings of falling. When man comes to take over what God has placed in the proper relationship, he destroys it. Since man has a relationship to himself, he must also have a relationship to the power that created that relationship, namely God. There is much evidence that it is the same ideas that are straining at the leash in Grundtvig’s thought. For Grundtvig man’s Self is his awareness of his dual relationship - the earthly, which the body gives expression to, and the divine, which the spirit shows. Grundtvig calls the former ‘royal’, the latter ‘vice-royal’. To embrace this dual relationship with thankfulness is the basic human law, the transgression of which results in man missing out on the prize (‘the crown’). But it is easy to see that man is tempted to transgress it by ‘enjoying his royal position’ and thereby ‘neglecting his servant’ relationship and thus ‘endeavouring for independence’. This is seen in the following quotation from Kierkegaard: Whatever man attempts to free himself from (with contempt for one half of the synthesis) he in reality allows himself to be bound by. But, according to Fibaek Jensen, whereas Kierkegaard tries to describe how the disparity arises, and how sin thereby enters the world, Grundtvig assumes the fall to be an indispensable, and as far as it goes, an inexplicable reality. He distinguishes between the internal and the external aspect of the fall. The aim of Grundtvig’s philosophical considerations is to describe the relationship between the spirit and the body in man, that is, between the inner and the outer senses, and thereby to demonstrate how an error in the development of those relations has resulted in a denial of man’s external dependence; since reason has torn itself free of the body and become autonomous, everything has become chaos. The fundamental anthropological model (fig. 1) is now at discord with itself, and Grundtvig now sees it as his task to a) prove this, b) show reason to its rightful place, show that it is only a part of man’s self. The problem was to get a dialogue going with his age, since it believed that reason was autonomous. On this point simple talk about God was not enough; Grundtvig had to move into the sphere of philosophy. Fibæk Jensen goes on to describe first Grundtvig’s strange conception of the relationship between the external and the internal senses, inasmuch as in his anthropology emotion, the power of the fantasy (that is, imaginative ability) and reason correspond to the senses of touch, sight and sound. Through the development of the inner senses, we raise the ‘Spirit’, which finds its expression in the ‘Word’, and with the development from foetus through birth to puberty we develop reason, which finds expression in ‘Art, Poetry and Scientific Knowledge’ (Konst, Poesie og Videnskabelighed’ (fig. 2)). Reason gathers within itself emotion, imaginative power and the intellect. It is not just abstract logic, but is dependent on the emotions. It is a link that synthesizes the inner senses interacting with the outer. But the development reveals at the same time an analogy with man’s relationship to God, inasmuch as the goal was that man ‘in a natural way’ should have reached the understanding that he ‘was an image of the eternal truth’. This can only happen now ‘in a supernatural way’, because we are no longer a true image of God in and of ourselves but only through faith in Christ (‘through the loving community with Him in the spirit’). - To reach such a point of view in an age that praised reason was no easy matter for Grundtvig. His criticism of the cosmology of romanticism was clearly directed against its monism, particularly in Schelling but also in Fichte and Kant. In his manifesto ‘On the century of philosophy’ (Danne-Virke I) Grundtvig selects the old Danish word ‘Vidskab’ (knowledge) instead of ‘Philosophie’ to denote the human endeavour towards total knowledge, that is, a complete explanation of the ‘reason and cause, the terms and meaning,* the intention and the goal’ of existence. These three links in Grundtvig’s philosophical endeavour are then studied by Fibæk Jensen one after the other. Grundtvig expressly points out beforehand that the goal is unattainable by man in mortal clay. The first question a thinking person must ask himself is, according to Grundtvig, whether at some time or other the first men and women were created by something that has been in existence for ever (God), or whether they themselves have been in existence for ever: ‘Whose are we?’ ‘Are we our own, or whose?’ According to Grundtvig the chain of cause and effect cannot be endless but must have a first, free and independent cause, God. Thus his answer to the first question is ‘that reason can never progress in the world through its own efforts, except to realize that in some incomprehensible way or other it must have been produced by a quite different reason.’ Human reason on the contrary ‘could comprehend itself and everything that belongs to that concept, that is all that belongs to temporal man and all that is temporal.’ To understand Grundtvig’s thoughts on this Fibæk Jensen has chosen a framework of three basic concepts in Grundtvig’s thought. In the ‘healthy human intellect and experience’ he finds his arguments against German idealism. The moment Reason repudiates the emotions’ immediate realization that there is a reality outside the individual observer, a decisive shift in the whole organization of man has taken place. Man’s task consists of realising consciously what the emotions spontaneously experience through the senses. Man must first understand that the body is and ought to be the image of the spirit, and then realise or believe that the whole man is a picture of the everlasting omnipotence. ‘We can comprehend only what has clearly entered into our consciousness of self. ’ But since consciousness of self is spontaneously sensual and only gradually (‘unspontaneously’) becomes ‘spiritual’, it becomes the task of man’s theory of knowledge to move from the spontaneous to the unspontaneous consciousness. Between these two phases lie experience and healthy human intellect. The healthy human intellect, according to Grundtvig, rests on experience. But Grundtvig also maintains that man ‘with his basic experience of body’ arrives at ‘the contradiction principle,’ his other major concept. Grundtvig regards as genuine contradictions (in contrast to contrary antitheses, which may be synthesized) ‘light and darkness, good and evil, truth and lying’. Particular reference can be made here to his dissertation ‘On Truth, Greatness and Beauty’. Here Fibaek Jensen quotes Henning Høirup on Christian Wolfs theory of knowledge: ‘All knowledge rests in reality on the fact that we cannot possibly imagine ourselves (or any other object) consciously and unconsciously at the same time.’ (Grundtvig’s View of Faith and Knowledge, 1949, p. 30). In his logical thought Grundtvig operates with a steady raising of consciousness, inasmuch as the basic principle of contradiction delineates the spontaneous sensual consciousness of self (that I am, in contrast to something else), whilst the ‘basic principle of cause and effect’ expresses the fact that through the power of imagination I have become conscious that I have removed myself from the original unity. But when I then ask with my intellect what the effect of this can teach us about the cause (namely God), then the foundaton for human life, according to Grundtvig, must be posited outside itself. The third basic concept in the enlightenment of temporal man is ‘History’, which builds on the Word, which is partly a connection between the body and the spirit, and partly - when it is written down - a link between the various historical epochs. The German idealists had not regarded history thus. They built systems without regard to it; but Grundtvig stuck to his main assertion: ‘that we do not comprehend one iota more of man than what Time has developed in us and illumined for us.’ All true ‘knowledge’, according to Grundtvig, must therefore be historical. Since human reason cannot therefore comprehend anything that is eternal and unchanging, the question of the intention and goal of human existence really falls outside the area of knowledge. Although Grundtvig is astonished at the calm with which his age regarded death, he can nevertheless prove nothing about life after death. Fibæk Jensen considers this a viable starting-point for a deeper understanding of man in his temporal circumstances (i.e. the limits of time). Not until reason relinquishes its independence, ‘will it settle under the wings of faith’, as Grundtvig says. Here Grundtvig depicts the movement that reason must make to break free o f ‘madness’. For if faith was only the ‘fruit of knowledge’, it would no longer be faith but only ‘the certainty of reason.’ In fig. 3 there is a schematic presentation of the task and limits of philosophy or ‘knowledge’ (Vidskab). According to Grundtvig, one must imagine that in the beginning there existed an unchanging basic being, (‘an eternal consciousness of self). Schelling’s error was to regard this primordial essence as being indifferent to good and evil. It cannot be indifferent to truth and lying. It must affirm both the light, the truth and the good. From this eternal the transition to the finite can only take place by a jump or a fall; Schelling proved this; but Grundtvig considers it ‘madness’ to suppose that this takes place in the godhead itself (as Schelling believed). Truth cannot deny itself. The fall, and therefore dualism, must therefore be posited in man. Recognition of the reality of the fall is Grundtvig’s starting-point. With the fall, time and place come into existence, and thus the possibility of change.